PENGELOLAAN DANA HAJI OLEH BADAN PENGELOLA KEUANGAN HAJI (BPKH) DALAM PERSPEKTIF KEADILAN - Efin Faridho (2022)
The research was carried out due to the gap between regulation and practice in managing the return of Hajj funds by the Hajj Finance Management Agency (BPKH). This thesis aims to provide an overview of fair management of hajj funds and the implementation of BPKH's responsibilities in managing hajj finances from a fairness perspective. The research uses library research, in which data and information are obtained from library sources (readings) in the form of books, dictionaries, encyclopedias, research results, news, and other reading media. The author employs both a normative and conceptual juridical approach in analyzing the data. Concerning the theoretical framework, the research uses the theory of justice and the theory of al-Maslahah al-Mursalah to address the research problem of Hajj Fund Management by BPKH from the perspective of justice. Based on the findings, this study concludes that the hajj funds managed by BPKH are in line with the principles of sharia in managing the investments but not fair in implementing the returns of the funds to the prospective pilgrims on the waiting list. The government is expected to be able to increase public trust by consistently improving the quality of the services and implementing fair Hajj fund management for prospective pilgrims on a waiting list. This Hajj fund has great potential, and its management should aim to provide beneficial returns to prospective pilgrims on the waiting list in particular and everyone in general.